2003
DOI: 10.1046/j.1365-3040.2003.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of metabolic changes by phosphorus stress in rice plant roots

Abstract: As most soil phosphates exist as insoluble inorganic phosphate and organic phosphates, higher plants have developed several strategies for adaptation to low phosphorus (P). These include the secretion of acid phosphatase and organic acids, induction of the inorganic phosphate (Pi) transporter and the substitution of some enzyme activities as alternative pathways to increase P utilization efficiency. It has been proposed that plants also have a ' pho regulon' system, as observed in yeast and Escherichia coli ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
180
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(198 citation statements)
references
References 54 publications
11
180
0
7
Order By: Relevance
“…In contrast, no significant change in APase activity in L. albus under high [CO 2 ] and high P supply was observed (Wasaki et al, 2003). This reduction in activity could be attributed to the higher concentration of P in root tissues.…”
Section: Accepted M Manuscriptmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, no significant change in APase activity in L. albus under high [CO 2 ] and high P supply was observed (Wasaki et al, 2003). This reduction in activity could be attributed to the higher concentration of P in root tissues.…”
Section: Accepted M Manuscriptmentioning
confidence: 78%
“…24 under P deficiency (Wasaki et al, 2003) showed up-regulation of genes related to glycolysis, alteration in lipid metabolism, modification of cell wall synthesis and changes in the metal responsive genes. Similarly, some glycolytic pathway related genes were induced in roots of L. albus under P starvation (Uhde-Stone et al, 2003a, b).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Phosphorus is an element required for plant growth, and an essential component of many chemical substances in plants such as phospholipids, nucleic acids, ATP and NADP, and is closely related to many metabolic processes in plants [44,45]. Nutrient control experiments on rice show that after reducing the phosphorus content of soil, the expression of enzymes related to cell-wall-synthesis increased significantly while the expression of enzymes related to lipolysis decreased [46]. A study of pigeon pea (Cajanus cajan) using isotope labeling shows a decrease of soil phosphorus could significantly inhibit the accumulation of non-structural carbohydrates [47].…”
Section: Effect Of Environmental Factors On Forage-quality Patternsmentioning
confidence: 99%
“…The Pi starvation-induced reprogramming of architecture and metabolism is supported by vast changes in the plant transcriptome and has been demonstrated in several plant models (Wasaki et al, 2003;Chiou and Lin, 2011;Hu and Chu, 2011;Huang et al, 2011). In Arabidopsis, more than 600 genes are induced in response to Pi starvation (Misson et al, 2005;Thibaud et al, 2010).…”
mentioning
confidence: 99%
“…For instance, SQD1 and SQD2 are involved in sulfolipid biosynthesis, whereas MGD2 and MGD3 are strongly induced to increase galactolipid content (Yu et al, 2002;Jouhet et al, 2004;Nakamura et al, 2005;Kobayashi et al, 2009). To achieve these substitutions, phospholipids are degraded by different types of lipases, resulting in the release of lipid subcomponents that can reenter the metabolism or be converted into other lipid forms (Nakamura, 2013).The Pi starvation-induced reprogramming of architecture and metabolism is supported by vast changes in the plant transcriptome and has been demonstrated in several plant models (Wasaki et al, 2003;Chiou and Lin, 2011;Hu and Chu, 2011;Huang et al, 2011). In Arabidopsis, more than 600 genes are induced in response to Pi starvation (Misson et al, 2005;Thibaud et al, 2010).…”
mentioning
confidence: 99%